Keteguhan Iman Dalam Era Tantangan Dari Perspektif Teologis Kristen - Melkisedek Melkisedek; Vera Agustin; Sandra R Tapilaha (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Firmness in faith is a human way of facing difficulties or challenges. Firmness of faith in difficult times is a concept from the perspective of Christian theology which focuses on the perseverance of individuals or Christian communities to maintain faith in the teachings of Christ amidst changing times. In this context, remaining strong in the faith requires a deep knowledge of Biblical truth, a commitment to following Christ's teachings, and a willingness to face trials and challenges that may arise. Through prayer, Bible reading, fellowship with fellow believers, and active participation in church, every Christian can strengthen their faith. The importance of unshakable faith in the perspective of Christian theology lies in its role as a solid spiritual foundation amidst current changes and temptations. By maintaining a strong faith, Christians can strengthen their relationship with God, find peace and strength in their faith, and become influential witnesses in society. Witnessing the strength of faith also inspires and strengthens the faith of fellow Christians and builds a strong community in faith and love for Christ. Therefore, from the perspective of Christian theology, strengthening faith in difficult times is not just an individual's effort to maintain faith, but also being a witness to Christ in the midst of an ever-changing world.